International practice for architects - Perkins, L. Bradford (John Wiley & Sons, 2008)
This is the primary reference for U.S. architects seeking to establish or expand their services in other countries. The book provides country-specific information on targeting foreign client groups and U.S. clients groups with projects abroad; contacting local professional organizations; deciphering foreign practice and licensing requirements; foreign building code and regulatory issues; customary contractual and fee arrangements; and establishing or enhancing relationships with local practitioners.